2021
DOI: 10.1080/03626784.2021.1915690
|View full text |Cite
|
Sign up to set email alerts
|

“More person, and, therefore, more satisfied and happy”: The affective economy of reading promotion in Chile

Abstract: Reading is often regarded as a public good and an essential part of developing almost every aspect of human potential. In this article, we survey the "affective economies" (Ahmed, 2004) of literary reading through a textual and visual analysis of documents issued by Chile's Ministry of Education. Through a critical and diffractive reading of these documents with Ahmed's and Braidotti's (2018) conceptualizations of the affective, we claim that when reading is presented as beneficial, pleasurable, and promising,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…The lack of association between emotional suppression and depressive symptoms is also inconsistent with previous findings [ 5 , 6 ]. It is possible that this lack of association is due to cultural issues such as, for example, a formal education that encourages reading that privileges the cognitive over the emotional and teaches to postpone any current negative effect for the promise of future happiness [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of association between emotional suppression and depressive symptoms is also inconsistent with previous findings [ 5 , 6 ]. It is possible that this lack of association is due to cultural issues such as, for example, a formal education that encourages reading that privileges the cognitive over the emotional and teaches to postpone any current negative effect for the promise of future happiness [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study carried out in Chile by Espinoza and Silva (2014) warned that young Chilean men have been socialized in a cultural system that favors the reproduction of a hegemonic model of masculinity based on a constant comparison and competition between emotional endurance and physical strength [ 67 ]. In another study conducted in Chile, it was observed that the formal education of boys and girls excludes readings that promote emotions such as sadness and anger, which could convey the idea that the expression of these emotions is not allowed [ 61 ].…”
Section: Discussionmentioning
confidence: 99%